Effect of modulation index of pulse width modulation inverter on total harmonic distortion for sinusoidal - Aboadla, Ezzidin Hassan Elmabrouk; Khan, Sheroz; Habaebi, Mohamed Hadi; Gunawan, Teddy Surya; Hamida, Belal Ahmed; Yaacob, Mashkuri (Institute of Electrical and Electronics Engineers Inc., 2016)
Knowing Total Harmonic Distortion (THD) of voltage source inverter (VSI) is important and must be within the allowable range. Several schemes are suggested to mitigate THD and to produce as much a sinusoidal output signal as would be possible. One of such schemes is using Sinusoidal Pulse Width Modulation (SPWM)-based inverter. SPWM is usually used in inverters for industrial applications. In this paper, a study of the performance of the SPWM technique is presented for a single phase H-bridge inverter. The SPWM scheme is modeled in MATLAB - Simulink. A bipolar and unipolar PWM technique are compared in this project as such techniques offer the features of effectively doubling the switching frequency of the output voltage. Under different conditions of modulation index, the pattern is utilised to estimate the harmonics. Simulation results for a full bridge single phase inverter using bipolar and unipolar SPWM are presented.